2018
DOI: 10.1108/ebhrm-04-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Job characteristics, job resources and work-related outcomes: role of person-organisation fit

Abstract: Purpose The purpose of this paper is to examine and understand the role of person-organisation (P-O) fit in mediating the relationship between job resources and work-related outcomes. The need to study the antecedents of P-O fit, dearth of its literature in India, and growing importance of ensuring congruence between the environment and the individual in a diverse workplace, to recruit and retain the employees, underlines the significance of this research. In addition to the mediating role of P-O fit, it was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 111 publications
0
8
0
1
Order By: Relevance
“…It is the balance between the abilities or desires of a person and the job requirements or attributes of a job. Priyadarshi and Premchandran (2018) had a view that the individuals who are selected according to the ability of the particular tasks are more likely to feel comfortable in performing those tasks and are more likely to be involved in their organization. Earlier researchers have revealed direct impact of P–J factors on work commitment (Farzaneh et al , 2014; Suifan, 2015; Therasa and Vijayabanu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is the balance between the abilities or desires of a person and the job requirements or attributes of a job. Priyadarshi and Premchandran (2018) had a view that the individuals who are selected according to the ability of the particular tasks are more likely to feel comfortable in performing those tasks and are more likely to be involved in their organization. Earlier researchers have revealed direct impact of P–J factors on work commitment (Farzaneh et al , 2014; Suifan, 2015; Therasa and Vijayabanu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the impact of cultural values on well-being concepts has been documented before (Li and Ngo, 2017;Priyadarshi and Premchandran, 2018). As a preface to the Thai work context, the current study acknowledges that Thailand is categorized as high in hierarchy, and low in autonomy and egalitarianism (Schwartz, 1999).…”
Section: Introductionmentioning
confidence: 79%
“…Extant empirical findings and theories seem to suggest P-O fit as a significant mediator on SHRPs, EE–OCB relationships (Presbitero et al , 2016). In an Indian study, Priyadarshi and Premchandran (2018) found a mediating effect of P-O fit on the coworker support–OCB relationship. Similarly, Mensah (2018) revealed that P-O fit partially mediates the relationship between talent management and employee attitudes among bank employees in Ghana.…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 93%
“…Put differently, P-O fit is used to explicate the level of congruence between employers and employees (Christiaans, 2013). Certainly, the appreciation of this concept is very important to any business undertaking in terms of improving employee engagement, job satisfaction (Priyadarshi and Premchandran, 2018), employee attitudes (Mensah, 2018), affective commitment (Kooij and Boon, 2017), reducing turnover intention (Memon et al , 2017) and most importantly, enhanced employee exhibition of extra role activities also known as organizational citizenship behavior (OCB) (Thomsen et al , 2016).…”
Section: Introductionmentioning
confidence: 99%